PENERAPAN PEMUNGGUTAN BEA PEROLEHAN HAK ATAS TANAH DAN BANGUNAN TERHADAP PERALIHAN HAK MELALUI JUAL BELI DI KABUPATEN SOLOK SELATAN DAN KOTA PARIAMAN - Rezi Yosrialde Putra; Yuslim Yuslim; Khairani Khairani (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, dan Pendidikan, 2023)
Law Number 28 of 2009 concerning Regional Taxes and Regional Levies explains that Land and Building Rights Acquisition Duty (BPHTB) is a tax on the acquisition of land and/or building rights. BPHTB levy procedures in South Solok Regency and Pariaman City, regulated based on Perbup and Perwako Number 13 of 2011 concerning the System and Procedure for Collecting Land and Building Rights Acquisition Duties, in Article 5 paragraph (1) taxpayers calculate and fill in their own BPHTB Regional Tax Deposit Letter (SSPD BPHTB). Taxpayers are required to calculate and fill in their own BPHTB SSPD. This is in line with the Self Assessment System. However, there are still many taxpayers who do not calculate and fill in the BPHTB SSPD themselves, but are more likely to submit it to PPAT, so that the mandate of Perbup and Perwako and the Self Assessment System tax collection system is not implemented. Even though it is submitted to PPAT, there are still taxpayers who commit tax fraud, by reducing the price of buying and selling transactions that actually occur with the transaction price stated in the BPHTB form requested by the taxpayer. The formulation of the problem in this study is: 1) How is the application of the levy of Land and Building Rights Acquisition Duty on the Transfer of Rights through Sale and Purchase in South Solok Regency and Pariaman City 2) How is the determination of land value as the basis for payment of Land and Building Rights Acquisition Duty on the Transfer of Rights through Sale and Purchase in South Solok Regency and Pariaman City. This research uses Empirical Juridical Research Methods, data used primary data and secondary data as well as data collection techniques in the form of interviews with parties related to this study. The implementation of BPHTB Levies in South Solok Regency and Pariaman City does not fully carry out the mandate of laws and regulations, namely Perbup and Perwako, where the regulations have stated that BPHTB management starting from filling in the BPHTB SSPD, calculations to depositing BPHTB owed is done by the taxpayer himself but it is not carried out, this happens because there is still a lack of taxpayer understanding of BPHTB management so that taxpayers look for other alternatives by submit the management of BPHTB to PPAT, and there are still taxpayers who commit tax fraud, by reducing the price of the actual sale and purchase transaction with the price stated on the requested BPHTB SSPB form, using 2 sales and purchase transaction receipts, one correct and one that has been reduced, in order to deceive the relevant SKPD and PPAT. Determination of land value, for the basis of BPHTB tax imposition is the Tax Object Acquisition Value (NPOP) and the Tax Object Acquisition Value (NPOP) is a sale and purchase transaction. However, in practice, the price of the sale and purchase transaction that has been agreed upon by the parties is not immediately granted by the relevant SKPD. However, it has other considerations, such as in South Solok based on the validation results, namely the Selling Value of Tax Objects (NJOP) and transaction prices, while in Pariaman it is carried out with considerations: 1) the value of buying and selling transactions 2) the Selling Value of Tax Objects (NJOP) 3) Market prices 4) The area or location of land 5) The economic value of the land 6) The type of soil 7) Going to the field.